Virus Sensor RIG-I Represses RNA Interference by Interacting with TRBP through LGP2 in Mammalian Cells - Tomoko Takahashi (Genes, 2018)
Exogenous double-stranded RNAs (dsRNAs) similar to viral RNAs induce antiviral RNA silencing or RNA interference (RNAi) in plants or invertebrates, whereas interferon (IFN) response is induced through activation of virus sensor proteins including Toll like receptor 3 (TLR3) or retinoic acid-inducible gene I (RIG-I) like receptors (RLRs) in mammalian cells. Both RNA silencing and IFN response are triggered by dsRNAs. However, the relationship between these two pathways has remained unclear. Laboratory of genetics and physiology 2 (LGP2) is one of the RLRs, but its function has remained unclear. Recently, we reported that LGP2 regulates endogenous microRNA-mediated RNA silencing by interacting with an RNA silencing enhancer, TAR-RNA binding protein (TRBP). Here, we investigated the contribution of other RLRs, RIG-I and melanoma-differentiation-associated gene 5 (MDA5), in the regulation of RNA silencing. We found that RIG-I, but not MDA5, also represses short hairpin RNA (shRNA)-induced RNAi by type-I IFN. Our finding suggests that RIG-I, but not MDA5, interacts with TRBP indirectly through LGP2 to function as an RNAi modulator in mammalian cells.